Janus particle-engineered structural lipiodol droplets for arterial embolization - Sijian Tao; Bingquan Lin; Houwang Zhou; Suinan Sha; Xiangrong Hao; Xuejiao Wang; Jianping Chen; Yangning Zhang; Jiahao Pan; Jiabin Xu; Junling Zeng; Ying Wang; et al. (Nature Communications, 2023)
Abstract Embolization (utilizing embolic materials to block blood vessels) has been considered one of the most promising strategies for clinical disease treatments. However, the existing embolic materials have poor embolization effectiveness, posing a great challenge to highly efficient embolization. In this study, we construct Janus particle-engineered structural lipiodol droplets by programming the self-assembly of Janus particles at the lipiodol-water interface. As a result, we achieve highly efficient renal embolization in rabbits. The obtained structural lipiodol droplets exhibit excellent mechanical stability and viscoelasticity, enabling them to closely pack together to efficiently embolize the feeding artery. They also feature good viscoelastic deformation capacities and can travel distally to embolize finer vasculatures down to 40 μm. After 14 days post-embolization, the Janus particle-engineered structural lipiodol droplets achieve efficient embolization without evidence of recanalization or non-target embolization, exhibiting embolization effectiveness superior to the clinical lipiodol-based emulsion. Our strategy provides an alternative approach to large-scale fabricate embolic materials for highly efficient embolization and exhibits good potential for clinical applications.